2013
DOI: 10.3390/ijms140816258
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antioxidation and Immunomodulation in Postnatal Multipotent Stem Cell-Mediated Cardiac Repair

Abstract: Oxidative stress and inflammation play major roles in the pathogenesis of coronary heart disease including myocardial infarction (MI). The pathological progression following MI is very complex and involves a number of cell populations including cells localized within the heart, as well as cells recruited from the circulation and other tissues that participate in inflammatory and reparative processes. These cells, with their secretory factors, have pleiotropic effects that depend on the stage of inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 128 publications
2
20
0
1
Order By: Relevance
“…As the Bio-Plex assay revealed, BMSCs cultured in hypoxia, compared to those cultured in normoxia, released significantly less pro-inflammatory cytokines (TNF-α, GM-CSF), more anti-inflammatory cytokines (IL-6, IL-10), and less pro-fibrotic cytokine (TGF-β1). Of particular interest, our data confirmed that hypoxic condition potentiated the production VEGF as it was also evidenced elsewhere [35, 36]. However, the inflammation network and cytokine cascades in myocardial infarction might, in fact, elaborate temporally and spatially in a complicated and dynamic pattern [32].…”
Section: Discussionsupporting
confidence: 71%
“…As the Bio-Plex assay revealed, BMSCs cultured in hypoxia, compared to those cultured in normoxia, released significantly less pro-inflammatory cytokines (TNF-α, GM-CSF), more anti-inflammatory cytokines (IL-6, IL-10), and less pro-fibrotic cytokine (TGF-β1). Of particular interest, our data confirmed that hypoxic condition potentiated the production VEGF as it was also evidenced elsewhere [35, 36]. However, the inflammation network and cytokine cascades in myocardial infarction might, in fact, elaborate temporally and spatially in a complicated and dynamic pattern [32].…”
Section: Discussionsupporting
confidence: 71%
“…Large amounts of reactive oxygen species produced by inflammatory cells invading the infarcted myocardium can cause massive cell death [49]. The spatiotemporal delivery approach employed in our study proved effective at reducing inflammation and promoting tissue repair.…”
Section: Discussionmentioning
confidence: 97%
“…Inflammatory cells can promote beneficial effects such as inducing angiogenesis by monocytes secreting proangiogenic factors and phagocytosis of dead cells and their cellular debris. However, they can also have detrimental effects on cell survival and cause tissue damage, infarct expansion, and LV dilation [60, 61]. Neutrophils produce large amount of reactive oxygen species (ROS) and elastase which cause cell apoptosis and elastin degradation [61, 62].…”
Section: Pathological Aspects Of MI and Corresponding Therapeutic mentioning
confidence: 99%
“…However, they can also have detrimental effects on cell survival and cause tissue damage, infarct expansion, and LV dilation [60, 61]. Neutrophils produce large amount of reactive oxygen species (ROS) and elastase which cause cell apoptosis and elastin degradation [61, 62]. In addition, they can reduce the proangiogenic effects of progenitor cells and bolster ischemic conditions [63, 64].…”
Section: Pathological Aspects Of MI and Corresponding Therapeutic mentioning
confidence: 99%
See 1 more Smart Citation